Evolution of parton distribution functions in the short-distance factorization scheme - Hervé Dutrieux; Joseph Karpie; Christopher Monahan; Kostas Orginos; Savvas Zafeiropoulos; on behalf of the HadStruc collaboration (Journal of High Energy Physics, 2024)
Abstract Lattice QCD offers the possibility of computing parton distributions from first principles, although not in the usual MS ¯ $$ \overline{MS} $$ factorization scheme. Calculations are therefore matched to MS ¯ $$ \overline{MS} $$ using a perturbative procedure which is the source of significant uncertainty within the currently accessible kinematics. We present the possibility of computing the z 2 evolution of non-singlet pseudo-parton distribution functions within the short factorization scheme in a numerically improvable way. The goal is to have tools to evolve a calculation to a scale where perturbative uncertainties are less pronounced. We compare a numerical extraction of the evolution operator from lattice data to the computation of z 2 dependence in perturbation theory. Finally, we discuss how this numerical work may be extended to address the two-scale problem that arises when the Ioffe time range must be made large to extend the reach of the calculation of the pseudo-PDF to smaller values of the momentum fraction.